Pengaruh Industrialisasi Terhadap Migrasi Per Propinsi di Indonesia Pada Tahun 2010 - Tatik Mariyanti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2010)
Tatik MariyantiFakultas Ekonomi Universitas TrisaktiEmail : tatik_m2002@yahoo.comAbstractThe title of this paper is the impact of industriiaization to migration by provinces in Indonesia on 2010. Today in Indonesia, there are still excess number of workers in the agriculture sector. The various sources clearly show the labor transformation in Indonesia still occur. Where as this transformation is a logical consequences for the developing country that carrying out the economic development. This condition also indicate with the excess labor in the capital intensive sector that relevan to the industrialization process. The experiences in some provinces show that migration to the urban area is related by the industrialization. The people migrate to the urban area in order to fullfill the labor needs in the industrial sector, because job in the industrial sectorwill give more added value compare with other sector such as agriculture sector. This research will anlyze the impact of industrialization to the migration by provinces in 2010.Based on theory and previous findings we estimate that there is influence of industrial sector employment, and wage rate toward migration between provinces in 2010, This research conclude that the contribution of industrial sector in regional GDP have a positive effect toward inter-provincial migration, the industrial sector contribution to employment has a effect on migration, and minimum regional wage rate have positive affect the migration significant at 5%. This test use Eviews-4, with multiple linear regression model.Keywords : Industrial sector, gross domestic product, employment, regional wage and migration